BOOK REVIEW: OBSlERVlING RACISM '1I'HROUGH WIDTENESS AND ITS ENTITLlEMENTS - Pratiwi Wini Artati (Celt: A Journal of Culture, English Language Teaching & Literature, 2008)
If only prejudices, stereotypes, and discrimination were totally diminished from this world, needless to say that peace is something that we could always breathe in and out easily, effortlessly. If only everyone did not focus on differences, everybody would have always lived in harmony for such a long time ago and in the future to come. Putting aside all differences and paying more attention the commonality and similarity that tightens the values of humanity is what we need. We often hear and imagine this will come true. Yet, the world is filled with discrimination in almost every aspect in human life.